Claudication Caused By Stenosis of Arteria Lusoria—Case Report and Review of Literature. Issue 12 (April 2019) - Tuleja, Aleksandra; Baumgartner, Iris; Schindewolf, Marc
Arteria lusoria is a rare vascular aberration; its presence is frequently associated with dysphagia or dyspnea due to esophageal or bronchial compression. We present a case of a stenotic arteria lusoria causing upper extremities blood pressure difference, claudication, and Raynaud's syndrome of the right hand. The patient opted against endovascular recanalization and was treated conservatively. This case demonstrates a rare cause of upper extremity blood pressure difference that must be considered as differential diagnosis. Furthermore, the knowledge of arteria lusoria is pivotal for successful transbrachial coronary or peripheral endovascular interventions.